Peran Bank Indonesia Terhadap Perlindungan Konsumen Ditinjau Dari Undang-Undang Nomor 4 Tahun 2023 Tentang Pengembangan Dan Penguatan Sektor Keuangan - Adilah Rahman; Esa Nur Hakam; Moch Rifan Juhendi; Farahdinny Siswajanthy (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This paper aims to analyze the role of Bank Indonesia in consumer protection, focusing on the legal framework of Law No. 4 of 2023 on Financial Sector Development and Strengthening. In the context of the changing dynamics of the financial sector, especially in an era that continues to evolve digitally, this research explores the impact and implementation of the regulation on the steps taken by Bank Indonesia in protecting consumer rights in the banking sector. This research uses a normative legal analysis method to identify and evaluate the role of Bank Indonesia in accordance with the provisions of Law No. 4 of 2023. The main focus is on the adjustment and improvement of regulations set by Bank Indonesia, especially Bank Indonesia Regulation Number 3 of 2023 concerning Bank Indonesia Consumer Protection which replaces Bank Indonesia Regulation Number 22/20/PBI/2020.